Characterization of Repetitive DNA in Saccharum officinarum and Saccharum spontaneum by Genome Sequencing and Cytological Assays - Wang, Kai; Xiang, Dong; Xia, Kai; Sun, Bo; Khurshid, Haris; Esh, Ayman M. H.; Zhang, Hui (Frontiers in Plant Science, 2022)
In most plant species, DNA repeated elements such as satellites and retrotransposons are composing the majority of their genomes. Saccharum officinarum (2n=8x=80) and S. spontaneum (2n=40-128) are the two fundamental donors of modern sugarcane cultivars. These two species are polyploids with large genome sizes and are enriched in repetitive elements. In this work, we adopted a de novo strategy to isolate highly repetitive and abundant sequences in S. officinarum LA Purple and S. spontaneum SES208. The findings obtained from alignment to the genome assemblies revealed that the vast majority of the repeats (97.9% in LA Purple and 96.5% in SES208) were dispersed in the respective genomes. Fluorescence in situ hybridization assays were performed on 27 representative repeats to investigate their distributions and abundances. The results showed that the copies of some highly repeated sequences, including rDNA and centromeric or telomeric repeats, were underestimated in current genome assemblies. The analysis of the raw read mapping strategy showed more copy numbers for all studied repeats, suggesting that copy number underestimation is common for highly repeated sequences in current genome assemblies of LA Purple and SES208. In addition, the data showed that the centromeric retrotransposons in all SES208 centromeres were absent in certain S. spontaneum clones with different ploidies. This rapid turnover of centromeric DNA in sugarcane provides new clues regarding the pattern of centromeric retrotransposon formation and accumulation.